The contribution of young people to raising social awareness among the community in an effort to achieve a harmonious social life - Ramadhani, Dina (Maliki Interdisciplinary Journal, 2026)
The growth of information and communication technology in today's digital world has greatly impacted social life, especially how young Muslims in Indonesia build their social identity. Social media is not just a way to talk to each other; it’s also a place where people can create meaning, share their values, and decide how they want to show themselves to the world. This study looks at how social media affects the way young Muslims shape their social identity. Additionally, this study looks at how young people contribute to increasing social awareness to help build a more peaceful community. This study uses a qualitative approach, which means it looks at information from different journals and important earlier research. The discussion shows that social media can affect how young people develop their social identity in both good and bad ways. Social media can help share ideas of kindness, support, and caring for other people. But, on the flip side, using social media too much can make us more self-centered, confused about our identity, and cause less face-to-face interaction with others. Young people, as agents of social change, are very important in bringing public attention to important issues. They accomplish this by engaging in different social events, educating the community, and using digital media for good reasons. Things like family, education, social surroundings, and social media play important roles in shaping how aware young people are about social issues. So, we should focus on improving character education, encourage young people to get involved in their communities, and use social media in a smart way to create a peaceful and accepting society that has a strong feeling of togetherness.